Consumers between supermarket shelves: The influence of inter-personal distance on consumer behavior. (September 2015) - Luck, Michael; Benkenstein, Martin
Abstract: Recent research underlines the important influence on consumer behavior of the mere presence of consumers on other consumers in retail businesses. While these results mainly relate to overall behavior, it is largely unknown how consumers behave in stores and how they react to customers present around them. This study examines the impact of an encounter between two consumers, directly in front of the same shelf row, on diverse consumer behavior. By means of two pilot studies we gained initial insights into the mutual influence. An image-based scenario study shows that the proximal distance is important for consumers' emotional state. In addition, the results indicate that these triggered negative and positive emotions mediate the effects of the distance on shopping satisfaction, aversive behavioral tendencies, willingness to buy, and number of alternatives considered. Highlights: We examine consumer behavior within a consumer encounter between supermarket shelves. We examine the influence of the distance between two consumers. Low interpersonal distance will increase/decrease negative/positive emotions. Low interpersonal distance will increase avoidance behavior. Low interpersonal distance will decrease relevant consumer behavior for retailers.